Introduction to Kojin Karatani's "Nationalism and Ecriture": Discussion Summary by Megan Becker-Leckrone - Derrida, Jacques; Becker-Leckrone, Megan (Surfaces, 1995)
In the context of the Second International Conference on Humanistic Discourse, this text introduces Kojin Karatani's "Nationalism and Écriture" and reports on the central concerns that emerged in its discussion.